Improving patient care and reducing the hospital acquired infection rate in ageing facilities - Pitso, M.E. (International Journal of Infection Control, 2007)
Despite structural and financial constraints, the infection control team at Barberton District Hospital implemented a series of infection control measures that successfully reduced the nosocomial infection rate from 8% in 2005 to 3.6% in 2006, and resulted in fewer cases of post-operative sepsis